1983
DOI: 10.1111/j.1365-2494.1983.tb01625.x
|View full text |Cite
|
Sign up to set email alerts
|

The production and persistency of different grass species cut at different heights

Abstract: The effect of two heights of cutting (5 and 8 cm) on the dry matter harvested and persistency of a range of different grass species and varieties were monitored over a 3-year period (1976 to 1978). Dry matter harvested was measured in the second and third harvest year and persistence of sown grass was assessed at the end of the first and third harvest year. The grasses were managed under a frequent cutting system, i.e. simulated grazing. Results showed that at the low cutting height tetraploid hybrid ryegrasse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1985
1985
2000
2000

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Different species and varieties (Jones, 1983) and genotypes (Harris, 1973) can show contrasting above-ground morphological adaptations to variations in cutting height and frequency. Plants grazed frequently can develop a short, prostrate canopy, which can be more resistant to grazing if less biomass is available to herbivores, and a greater amount of photosynthetic and meristematic tissue remains available for regrowth following defoliation.…”
Section: Species Herbivore and Fertility Interactionsmentioning
confidence: 99%
“…Different species and varieties (Jones, 1983) and genotypes (Harris, 1973) can show contrasting above-ground morphological adaptations to variations in cutting height and frequency. Plants grazed frequently can develop a short, prostrate canopy, which can be more resistant to grazing if less biomass is available to herbivores, and a greater amount of photosynthetic and meristematic tissue remains available for regrowth following defoliation.…”
Section: Species Herbivore and Fertility Interactionsmentioning
confidence: 99%
“…in the extent of diurnal variation in temperature (Peacock 1975). A shoot apex as low as that of tall fescue (12-15 mm below ground level in established swards) is presumably well insulated and well protected from defoliation and this could be an important reason for its ability to survive fairly close defoliation (Jones 1983), severe winter conditions (Spedding & Diekmahns 1972) and drought (Hughes et al 1977). The ryegrasses have higher apices and, in hybrid and Italian varieties at least, are more susceptible to close defoliation (Jones 1983), winter damage (Scottish Agricultural Colleges 1984) and drought (Hughes et al 1977).…”
Section: Position Of Shoot Apexmentioning
confidence: 99%
“…A shoot apex as low as that of tall fescue (12-15 mm below ground level in established swards) is presumably well insulated and well protected from defoliation and this could be an important reason for its ability to survive fairly close defoliation (Jones 1983), severe winter conditions (Spedding & Diekmahns 1972) and drought (Hughes et al 1977). The ryegrasses have higher apices and, in hybrid and Italian varieties at least, are more susceptible to close defoliation (Jones 1983), winter damage (Scottish Agricultural Colleges 1984) and drought (Hughes et al 1977). Timothy, which is noted for its winter-hardiness, evidently has its apices close to ground level in winter and protected by relatively large numbers of leaf sheaths (judging from the number of live, emerged leaves per tiller (Table 2)) and unemerged leaves.…”
Section: Position Of Shoot Apexmentioning
confidence: 99%
“…This singlechop system did not, however, show any signs of compensation through increased stubble yield although this may have been confounded by the lower cutting height achieved on this system at the first harvest. However, it is accepted that Jones (1983) concluded that there was no adverse effect of cutting height of a flail harvester (50 mm v. 80 mm) on herbage production from perennial ryegrass swards.…”
Section: Available Herbagementioning
confidence: 99%